2006
DOI: 10.2214/ajr.05.0562
|View full text |Cite
|
Sign up to set email alerts
|

MDCT Angiography of the Spinal Vasculature and the Artery of Adamkiewicz

Abstract: Contrast-enhanced 40-MDCT technology, in combination with an adapted brain reconstruction algorithm, can depict the artery of Adamkiewicz and its anatomic variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 24 publications
1
60
2
3
Order By: Relevance
“…Posterior branch of the radicular artery posterior radicular a., 9,10,20 medullary a., 12 posterior medullary a., 18 posterior radiculomedullary aa., 16 a. radicular posterior, 19 posterior segmental medullary a. Anterior spinal artery a. spinalis anterior; 5,6 anterior spinal a., [12][13][14]18 anterior median spinal a., 10 anterior long spinal a. Artéria espinhal anterior (TA)…”
Section: Review Of the Literatureunclassified
“…Posterior branch of the radicular artery posterior radicular a., 9,10,20 medullary a., 12 posterior medullary a., 18 posterior radiculomedullary aa., 16 a. radicular posterior, 19 posterior segmental medullary a. Anterior spinal artery a. spinalis anterior; 5,6 anterior spinal a., [12][13][14]18 anterior median spinal a., 10 anterior long spinal a. Artéria espinhal anterior (TA)…”
Section: Review Of the Literatureunclassified
“…2 Boll et al reported that using a brain reconstruction system can minimize beam hardening artefacts from high-density osseous structures and obscuration of sharp delineation of vasculature. 10 In contrast, in the present study a standard examination protocol was used without using any additional software. 10 Yoshioka et al used their CTA automatic triggering system for a delayed scan of a 10 mm region of interest (ROI) located in the descending aorta at the level of T7.…”
Section: Discussionmentioning
confidence: 97%
“…10 In contrast, in the present study a standard examination protocol was used without using any additional software. 10 Yoshioka et al used their CTA automatic triggering system for a delayed scan of a 10 mm region of interest (ROI) located in the descending aorta at the level of T7. In their study, aortic density was measured 3 times per s, and when the value reached a point of 130 HU, a helical CT began automatic scanning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations